Reproductive performance of murrah buffaloes - SAINI, M S; PANDER, B L; YADAV, R S; GREWAL, S S; SINGH, N (The Indian Journal of Animal Reproduction, 2023)
Data on 744 Murah buffaloes maintained at Buffalo Research Centre, CCS Haryana Agricultural University, Hisar from the year 1993-94 to 2000-2001 were analysed for studying the trends in reproductive traits. A significant decrease in age at first calving (AFC) was observed over the years, the age decreased from 1570 (during 1993-94) to 1440 days (during 1999-2000). No definite pattern was observed in case of service period (SP) over the years, however, it ranged from 107 to 163 days. A similar trend was observed in calving interval (Cl), it ranged from 409 to 479 days. Calving interval and service period improved in favourable direction with advancement of parity.